The problem of pure consciousness : mysticism and philosophy - Forman, Robert K. C. (Oxford University Press, 1997)
Are mystical experiences formed by the mystic's cultural background and concepts, as ""constructivists"" maintain, or do mystics sometimes transcend language, belief, and culturally conditioned expectations? Do mystical experiences differ throughout the various religious traditions, as""pluralists"" contend, or are they somehow ecumenical? The contributors to this collection scrutinize a common mystical experience, the ""pure consciousness event""--The experience of being awake but devoid of intentional content--in order to answer these questions. Through the use of historical Hindu, Buddhist,